Condition monitoring of lift system - Chew, Jonathan Cheng Yang (Nanyang Technological University, 2023)
This Final Year Project (FYP) aims to analyse the viability of performing condition monitoring for electric lift systems in Singapore, with the implementation of a prototype system to detect, collect and analyse the data obtained from a mock-up lift door subsystem. The journey towards remote monitoring and pre-emptive lift maintenance is still a work-in-progress, with the Building and Construction Authority (BCA) spearheading a Code of Practice recently in 2022.